2021
DOI: 10.1002/iub.2472
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic transcripts of LINC01311 and hsa‐miR‐146a‐5p regulate neural development in a cellular model of Alzheimer's disease

Abstract: Emerging evidence has shown that Long noncoding RNAs (LncRNAs) are aberrantly expressed and functionally involved in the development of neurodegenerative disorders. In this work, we investigated the regulatory effects of lncRNA of LINC01311 and its competing endogenous RNA target of hsa‐miR‐146a‐5p in a cellular model of Alzheimer's disease (AD). SH‐SY5Y cells were treated with synthetic Βeta‐Amyloid Peptide (1‐42) (AB1‐42) in vitro to induce AD‐like neural injuries. Expressions of LINC01311 and hsa‐miR‐146a‐5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Further experiments showed that LINC01311 promotes proliferation and reduces apoptosis and autophagy by sponging miR-146a-5p (Table S1). Consistent with these findings, upregulation of this miRNA was observed in AD patients and AD animals [91].…”
Section: Alzheimer's Disease (Ad)supporting
confidence: 84%
“…Further experiments showed that LINC01311 promotes proliferation and reduces apoptosis and autophagy by sponging miR-146a-5p (Table S1). Consistent with these findings, upregulation of this miRNA was observed in AD patients and AD animals [91].…”
Section: Alzheimer's Disease (Ad)supporting
confidence: 84%
“…The full texts of the remaining 34 articles were evaluated, and 20 more articles were also excluded because they did not validate the components of the ceRNA loop using molecular techniques ( Wang et al, 2017 ; Yu et al, 2018 ; Zhou et al, 2019 ; Ma et al, 2020 ; Xu and Jia, 2020 ; Huaying et al, 2021 ; Lu et al, 2021 ; Ou et al, 2021 ; Tang et al, 2021 ; Zhang et al, 2021 ) and did not use human specimens or cell lines ( Jiang et al, 2016 ; Cai et al, 2017 ; Wang J. et al, 2018 ; Wang X. et al, 2018 ; Ma P. et al, 2019 ; Zhao et al, 2019 ; Li L. et al, 2020 ; Li X. et al, 2020 ; Yue et al, 2020 ; Zhou et al, 2020 ). Lastly, a total of 14 eligible articles remained ( Faghihi et al, 2010 ; Ke et al, 2019 ; Wang et al, 2019 ; Zeng et al, 2019 ; Zhu et al, 2019 ; Gao et al, 2020 ; Ge et al, 2020 ; Gu et al, 2020 , 2021 ; He W. et al, 2020 ; Yan et al, 2020 ; Yue et al, 2020 ; Fan et al, 2021 ; Zhang and Wang, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…All but one study ( Faghihi et al, 2010 ) was conducted in China. Eleven studies examined the ceRNA regulatory loop on human cell lines ( Ke et al, 2019 ; Wang et al, 2019 ; Zeng et al, 2019 ; Zhu et al, 2019 ; Gao et al, 2020 ; Ge et al, 2020 ; Gu et al, 2020 , 2021 ; Yan et al, 2020 ; Yue et al, 2020 ; Fan et al, 2021 ) and three on both human specimens and cell lines ( Faghihi et al, 2010 ; He W. et al, 2020 ; Zhang and Wang, 2021 ). All studies with human specimens had a case-control design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations